Periodotnal health status and treatment needs among Iraqi dental students - AL- Muhamadawy, Abdul- Karim A. A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: periodontal disease are the major risk factors for tooth loos in aged persons. Clinically, patients with gingivitis or periodontitis usually suffer from gingival bleeding and periodontal probing. Material and method: The human sample consisted of five hundred and ninety eight students, 208 males and 390 females. Russel’s periodontal index (PI) plaque index (PI. I) and the periodental treatment need system (PTNS) were scored. Results: The mean PI and P1.I for males were 1.94, 1.72 respectively. For females the corresponding values were 1.73. 1.49. From the total sample 2.4% males and 6.1% females were in no need of periodontal therapy.A comparison between first and final year students showed for all indices used a statistically highly significant differences (P<0.01). Conclusions: Although an improvement in all indices does occur, but still more emphasis should be placed on prevention through out the dental on curriculum.